Spousal Influence on CPAP Adherence: Applications of Health‐related Social Control. Issue 8 (August 2016) - Mead, Michael P.; Irish, Leah A.
Abstract: Obstructive sleep apnea (OSA) is one of the most prevalent sleep disorders in the United Sates and is a risk factor for poor health outcomes. Continuous positive airway pressure (CPAP) therapy is an effective treatment for OSA, but adherence rates are poor. Although the spouses of patients with OSA have high potential to influence adherence, there has been minimal research to date. The purpose of this review is to summarize key findings regarding spousal influence on health‐related behavior change and treatment adherence from other medical fields (e.g., type 2 diabetes and cardiovascular disease) in which this line of inquiry has been more thoroughly developed. Recommendations are presented to guide future research investigating spousal influence on CPAP adherence based on findings from other patient populations. In particular, we emphasize the use of spousal health‐related social control as it applies to adherence and provide guidance regarding conceptual and methodological moderators.